Deus X - Jones, Stephen Mack (The August Snow novels ;, 2023)
"Father Michael Grabowski, a Franciscan priest who has tended the spiritual needs of Detroit's Mexicantown for forty years, has suddenly retired. August Snow, who has known the priest his whole life, finds the circumstances troubling--especially in light of the recent suspicious suicide of another local priest. What dark history is Father Grabowski hiding? The situation takes a turn for the deadly with the appearance at the Detroit diocese of a mysterious priest and combat vet calling himself Francis Dominioni Petra. The man comes from the Vatican, and as his armored guard circles closer and closer to Father Grabowski and his friends, August wants to know why. A terrible crime has been committed in the name of faith-but who is seeking justice, and who is trying to bury the truth and any of its witnesses? August grapples with his own ideas about his faith and his chosen family in this action-packed fourth installment in the Hammett Prize-winning series"--